Implementasi Bimbingan Konseling Islam Terhadap pengembangan Akhlak Siswa SMP - Syafiq, Mohamad; Syafi'i, M. Anton (Afkaruna: International Journal of Islamic Studies (AIJIS), 2023)
This study aims to determine the implementation of counseling guidance on student moral development in Muhammdiyah 5 Lekok Middle School. This study uses a qualitative approach with the type of research on case studies. The results of the study concluded that: (1) the implementation of counseling guidance programs on student moral development by providing group counseling, collecting student problems, evaluating activities; (2) Supporting factors for the implementation of counseling guidance include adequate facilities, cooperation between all parties, as well as counselors' duties are held by people who are experts in the field of counseling; (3) obstacles to the implementation of counseling guidance include, among others, lack of synergistic between counseling guidance teachers and several parties, lack of cooperation from parents of students, the principle of honesty that has not been fulfilled, the negative views of children about counseling guidance; (4) Student personality after getting counseling guidance services experiences moral development for the better, such as learning and worship problems, school rules, polite and more diligent and use free time to learn.